HUBUNGAN PENGETAHUAN SISWA TENTANG DAMPAK ROKOK TERHADAP KESEHATAN DENGAN PERILAKU MEROKOK DI SMA SATAP 4 GUNUNGSARI LOMBOK BARAT TAHUN 2019 - Juniati Juniati; Suswinda Yulisutomo; Hersika Asmawariza (LPPM STIKES Muhammadiyah Kendal, 2019)
Smoking is a very detrimental behavior. For the culprit smoking can cause various diseases such as high blood pressure and heart disease which is caused by the influence of chemicals contained in cigarettes such as nicotine and tar. West Nusa Tenggara ranks sixth for the highest national percentage of first-time smoking, aged 15-19 years 43.3%, 20-24 years 14.6%. The research design used in this study was to use a cross sectional approach. The population in this study amounted to 77 people. Sampling was carried out using purposive sampling, amounting to 30 people, but in sampling there were exclusion criteria so that the total sample was 30 respondents. The research instrument used a questionnaire. Data analysis techniques used the chi-square test α = 0.05.The results showed that most of the less knowledgeed as many as 14 people (46.7%) who had good knowledge as many as 5 (16.7%) and who were knowledgeable enough 11 (36.7%) Results of the chi-square test α = 0.05 obtained p = 0,000 <0.05 so that Ha is accepted, meaning that there is a relationship between students' knowledge about the impact of smoking on health with smoking behavior at SATAP 4 Gunungsari High School.So it can be concluded that there is a relationship between students' knowledge about the impact of smoking on health with smoking behavior in SMA SATAP 4 Gunungsari Barat Lombok Regency in 2019.